Our aging bodies - Merrill, Gary F. (Rutgers University Press, 2015)
"People in developed countries are living longer and, just as the aged population around the world is steadily growing, the number of adults eighty-five and older in the United States is projected to quadruple to twenty-one million people by 2050. The aging of our population has huge implications for baby boomers and their children, and has generated a greater interest in the causes and effects of aging. Our Aging Bodies provides a clear, scientifically based explanation of what happens to all the major organ systems and bodily processes--such as the cardiovascular and digestive systems--as people age. The first section is an overview of secondary aging--changes that occur with age that are related to disease and the environment--and include the effect of such things as diet, humor, and exercise. Readers will also learn about primary aging--intrinsic changes that occur with the aging of specific organs and body systems (including the prostate, the heart, the digestive system, and the brain). Throughout the book, Gary F. Merrill weaves in personal anecdotes and stories that help clarify and reinforce the facts and principles of the underlying scientific processes and explanations. Our Aging Bodies is accessible to a general reader interested in the aging phenomenon, or baby boomers wanting to be more informed when seeing their doctor and discussing changes to their bodies as they age"--Publisher's description